Pelatihan Akupresur Kader Lansia Guna Meningkatkan Imunitas di Desa Penatarsewu Tanggulangin Sidoarjo - Amelia, Paramitha; Setiawan, Hamzah; Wicaksono, Arief; Cholifah, Siti; Jakaria, Ribangun Bamban (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
This Covid-19 pandemic has a multidimensional impact on life, especially elderly who face a significant risk of contracting Covid-19. Several ways to increase immunity, especially elderly, include nutritious food, increase activity, and acupressure. The purpose of research is to provide acupressure training for elderly cadres to increase immunity of elderly during Covid-19 pandemic. The stages of implementing acupressure training were the survey service team to partner locations, collaborate with village government, midwives and elderly cadres then plan concept of solutions and stages. The team made media in form of posters of acupressure points and leaflets of acupressure points for hands and body. The result of community service, namely attitude of participants about acupressure has increased from attitude of the good category 11 people (73%) to very good as many as 14 participants (93%). The skills of participants, namely that before training did not have acupressure skills and after training all participants had acupressure skills. Number of participants who have skills to determine acupressure points correctly is 13 people (86%) and participants who can do acupressure correctly are 12 people (80%).